GENERATING A SEAMLESS TILING OF A NATURE IMAGE - Hartanto, Budi (Institute of Research and Community Outreach - Petra Christian University, 2007)
Tiling is a process to create a repetitive - larger size - image. However if the picture on the left side of the original image is not continuous to the picture on its right side, the tiling image will have a virtual vertical line called seam. Meanwhile the virtual horizontal line will appear if the picture on the top side of the original image is not continuous to the picture on its bottom side. The research performed here tries to generate a seamless tiling image by finding the closest match of the fractional source image to the partially build resulted image. From the experiment, it can be shown that the quality of the resulted image are affected by the number of similar elements in the source image, the number of fractional images created from the source image, and the width of the overlap area. Source image with a lot of similar element, high number of fractional images, and wider size of the overlap area have been proven to yield a seamless tiling image.